Jan Karski : from eyewitness to moral witness - Becker, Annette (1953- ). (2015)
Zakres i treść: the eyewitness "Here is the jeremiad of western civilization, realistic, appalling", from eyewitness to moral witness, toward a self-judaisation, conclusion: Karski - "The righteous among the nations".
Tyt. nagł.
Streszcz. pol.